Toepassing van motoriek-toetse op skoolkinders van 6-12 jaar - Jordaan, H. E; Holl, B. M; Neethling, E. M (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B. Ed. Ph.) -- Universiteit van Stellenbosch, 1948.